Sacrococcygeal teratoma in one twin: a case report and literature review - Qing Hu; Yiyun Yan; Hua Liao; Hongyan Liu; Haiyan Yu; Fumin Zhao (BMC, 2020)
Abstract Background Sacrococcygeal teratoma is one of the most common congenital tumors in newborns and infancy. The incidence is 1 per 20,000-40,000 live births. Ultrasonography is an optimal method for prenatal screening and diagnosis of fetal sacrococcygeal teratoma. MRI can be used to assist in the diagnosis. However, sacrococcygeal teratoma in the twin pregnancy is rare. Case presentation We reported a case of one twin with sacrococcygeal teratoma in dichorionic-diamniotic twin pregnancy.One twin with sacrococcygeal teratoma was diagnosed at the second trimester by ultrasonic examination and another twin was normal. A regular and careful antenatal care was conducted by the multidisciplinary team. The parents refused to perform the fetal MRI and examine the chromosome of both twin.At 37 + 1 of gestation, planned cesarean section was performed. The healthy male co-twin (twin A) weighed 2880 g.The male twin with SCT (twin B) weighed 2900 g, complying with 6 × 3 × 3 cm cystic and solid mass in sacrococcygeal region. At four days of age twin B underwent excisional surgery of the sacrococcygeal teratoma and coccyx and discharged 7 days after surgery. The mother and both babies were followed up and are all in good health until now. Conclusion(s) Sacrococcygeal teratoma in twin pregnancy is rare. Early antenatal diagnosis is important. Once the sacrococcygeal teratoma is diagnosed, clinicians should be aware of the associated maternal and fetal complications. Expecting parents should be counseled by the multidisciplinary team about the management and prognosis of the STC twin and co-twin. Prompt surgical excision of the sacrococcygeal teratoma after birth should be suggested.